PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR SAMSAT KABUPATEN GOWA - Bahri, Syamsul (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine how the effect of compensation and work discipline on the Employee Performance of the employees at Samsat Gowa Offices. The population in this study were employees of the Samsat Gowa Office and the sample used was 30 people using a saturated sample. Data was collected by using observation and questionnaire methods. The data analysis technique used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS). The results of this study indicate that compensation and work discipline have a significant effect on the performance of the employees at Samsat Gowa Offices and simultaneously compensation has a significant effect on employee performance and work discipline has a significant effect on the performance of the employees at Samsat Gowa Offices